Pemikiran Mohammad Hatta Tentang Pendidikan Islam - Utomo, Ilham Nur; Wijayanti, Dwi (Tribakti: Jurnal Pemikiran Keislaman, 2020)
This paper analyzes Mohammad Hatta's idea of modern Islamic education. Mohammad Hatta is not only known as a national figure and the first Indonesian vice president, but also a faithful, active individual in the field of Islamic education. He also expresses his idea regarding Islamic education in papers. Islamic education discourse still emerges as an important discussion topic today. This paper is the result of a qualitative study with literature review. The study aimed to discover Mohammad Hatta’s idea of modern Islamic education, which still emerges as a problem in today's Indonesian Islamic education. In this case, it is necessary to provide a representative, modern Islamic education in order to deliver ideal Muslim scholars. The study found that the construct of Mohammad Hatta’s idea on modern Islamic education was to create coherence between religion and modern science, comprising sociology, history, and philosophy. Such an idea is not merely an abstract, it was applied through the establishment of Sekolah Tinggi Islam (Islamic College) in 1945 as a modern Islamic higher education.